Respon Strategis Rumah Sakit terhadap Dinamika Sistem Pembayaran INA-CBG dalam Era BPJS Kesehatan: Literature Review⁠ - Denis Radiansyah Kustiwa; Mokhamad Syifa Haykal Azizi; Purwadhi Purwadhi; Yani Restiani Widjadja (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
The implementation of the Indonesia Case Base Groups (INA-CBG’s) payment system under the National Health Insurance scheme has fundamentally altered hospital financial and operational dynamics. This study aims to analyze hospitals’ strategic responses to the evolving challenges of the INA-CBG’s payment system within the BPJS Kesehatan era. A Systematic Literature Review (SLR) approach was employed by reviewing 42 national and international scientific articles published between 2014 and 2025, retrieved from Scopus, Web of Science, Google Scholar, and Sinta databases, following PRISMA guidelines. The synthesis of findings indicates that the prospective case-based payment system generates significant implications for hospital management, particularly in cost control, claim management, operational efficiency, and organizational adaptation. Hospitals’ strategic responses are reflected in strengthening financial governance, optimizing service processes, improving clinical documentation accuracy, enhancing information systems, and adjusting organizational policies. Key challenges identified include tariff adequacy, financial risk, administrative complexity, and potential tensions between efficiency and service quality. The findings highlight that hospitals with stronger managerial capacity and integrated information systems demonstrate better adaptability to payment system dynamics. This study underscores the importance of strategic and managerial readiness in sustaining hospital performance and service continuity within a prospective payment environment.